2022
DOI: 10.1155/2022/2995464
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of GeneXpert MTB/RIF, Gene Chip Technology, and Modified Roche Culture Method in Detecting Mycobacterium tuberculosis and Drug Susceptibility in Sputum

Abstract: Our aim of this study was to observe and analyze the performance of the real-time fluorescence quantitative nucleic acid amplification detection of Mycobacterium tuberculosis/rifampicin resistance (GeneXpert MTB/RIF), gene chip technology, and modified Roche culture method in detecting MTB in sputum submitted for inspection and drug susceptibility. Patients with smear-negative suspected pulmonary TB (n = 120) in our hospital were enrolled in this study using a random number table, and sputum samples submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…A previous study suggested that the GeneXpert MTB/RIF assay and culture had similar results in sputum-negative patients, [ 13 ] while another study showed higher performance of the GeneXpert MTB/RIF assay compared to culture in sputum. [ 6 ] Hence, the selection of culture as the gold standard in this study might influence the results. However, the GeneXpert MTB/RIF assay still had undeniable advantages over culture due to its simultaneous detection of M. tuberculosis and rifampicin resistance, rapid testing of within 2 hours, and the involvement of minimal manipulations and hence minimal biohazard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that the GeneXpert MTB/RIF assay and culture had similar results in sputum-negative patients, [ 13 ] while another study showed higher performance of the GeneXpert MTB/RIF assay compared to culture in sputum. [ 6 ] Hence, the selection of culture as the gold standard in this study might influence the results. However, the GeneXpert MTB/RIF assay still had undeniable advantages over culture due to its simultaneous detection of M. tuberculosis and rifampicin resistance, rapid testing of within 2 hours, and the involvement of minimal manipulations and hence minimal biohazard.…”
Section: Discussionmentioning
confidence: 99%
“…The GeneXpert MTB/Rif and gene chip assays were reported to be more sensitive than culture for detecting M. tuberculosis in sputum. [ 6 ] The GeneXpert MTB/Rif assay also tended to be more accurate than AFB. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados enfatizan la necesidad de continuar con la investigación y evaluación del desempeño diagnóstico de GeneXpert MTB/RIF, así como de las nuevas versiones que se introducen en el mercado 15,16,17 . Es vital considerar las variables demográficas, clínicas y microbiológicas específicas de poblaciones como la ecuatoriana para optimizar el uso de herramientas diagnósticas en la lucha contra la tuberculosis, facilitando así una detección más precisa y un manejo adecuado de esta enfermedad a nivel global 18,19,20…”
Section: Discussionunclassified
“…In the field of microbiology, gene chip technology has been used in the study of microbial functional genomics, biological pathogenic mechanisms, infectious disease diagnosis, environmental microbial detection, etc . 50 , 51 , 52 For example, gene chip technology that helps improve the diagnostic efficiency of the detection of drug-resistant Mycobacterium tuberculosis in clinical sputum samples could be directly used in the diagnosis of drug-resistant tuberculosis. 53 …”
Section: The Development History Of Microbial Sequencingmentioning
confidence: 99%